Effect of simultaneous addition of ferroniobium and ferrotitanium on properties of hardfacing. Issue 18 (12th December 2018) - Liu, Dashuang; Wu, Mingfang; Long, Weimin; Li, Leijun; Wei, Ping
ABSTRACT: The slag-free self-shielded flux-cored wire with simultaneous addition of ferroniobium (Fe-Nb) and ferrotitanium (Fe-Ti) was developed to fabricate the iron-based hardfacing alloys. The transfer coefficients of Nb and titanium of slag-free self-shielded flux-cored wire were 91.2 and 63.8%, respectively. The changes in microstructures indicate that Nb and Ti addition shifted the carbon concentration in the remaining liquid to one corresponding to the near eutectic state owing to the formation of (Nb, Ti)C which consumed carbon. The wear loss of the hardfacing alloy with 18 wt-% Fe-Nb and 6 wt-% Fe-Ti addition was the smallest among all the alloys owing to the formation of reinforced uniform quadrangle-shaped (Nb, Ti)C carbides in the refined microstructure and the highest hardness.